2019
DOI: 10.1007/s12307-019-00232-2
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-Infiltrating Immunosuppressive Cells in Cancer-Cell Plasticity, Tumor Progression and Therapy Response

Abstract: In most tumors, cancer cells show the ability to dynamically transit from a non-cancer stem-like cell to a cancer stem-like cell (CSC) state and vice versa. This cell plasticity has been associated with the epithelial-to-mesenchymal transition program (EMT) and can be regulated by tumor cell-intrinsic mechanisms and complex interactions with various tumor microenvironment (TME) components. These interactions favor the generation of a specific "CSC niche" that helps maintain the main properties, phenotypic plas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
61
0
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(70 citation statements)
references
References 161 publications
(168 reference statements)
1
61
0
8
Order By: Relevance
“…The subset of CSCs deputed to metastasis initiation possesses features allowing primary tumor escape, survival in circulation, and distant organs seeding ( 50 , 51 ). Immune escape mechanisms adopted by MICs are supposed to be essential to complete all the steps leading to metastasis generation ( 52 , 53 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The subset of CSCs deputed to metastasis initiation possesses features allowing primary tumor escape, survival in circulation, and distant organs seeding ( 50 , 51 ). Immune escape mechanisms adopted by MICs are supposed to be essential to complete all the steps leading to metastasis generation ( 52 , 53 ).…”
Section: Discussionmentioning
confidence: 99%
“…Some evidence has reported that CSCs are characterized by specific immunological properties, which protect them against chemotherapeutic drugs but also increase their resistance toward apoptosis-inducing immune effectors, like T or NK cells ( 54 ). Several mechanisms can be exploited by CSCs to escape immune surveillance, such as down-regulation of MHC class I and II molecules, inefficient antigen presentation, and release of immunosuppressive factors ( 52 ). These strategies would help CSCs to survive, sustain tumor progression, and metastasize ( 53 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Engineered lymphocytes have to traverse abnormal tumor vasculature with reduced adhesion molecules, experience chemokine/chemokine receptor mismatch (8), and must migrate through dense cellular and stromal barriers. Upon ingress into the TME, effector cells encounter unfavorable conditions such as a hypoxic and acidic environment (9), expression of immune checkpoint ligands (10,11), and an abundance of immunosuppressive cells such as tumor associated macrophages (TAMs), myeloid derived suppressor cells (MDSCs), and regulatory T cells (T-regs) (12). Additionally, chronic antigen engagement can lead to T cell exhaustion, decreasing the effector function of CAR T cells (13).…”
mentioning
confidence: 99%
“…Immunotherapy is effective for patients with melanoma, leukemia and other solid tumors ( 7 10 ). The importance of lymphocytes and tumor-associated macrophages (TAMs) in the tumor microenvironment has been assessed and is considered a key factor of immunotherapy response ( 11 , 12 ). However, little is known about the comprehensive immune infiltration in brain tumor, particularly in MB.…”
Section: Introductionmentioning
confidence: 99%